Self-powered visible light detector based on BiVO4-BaTiO3 composite film and preparation method thereof

The self-powered visible light detector with BiVO4-BaTiO3 composite thin film structure solves the problems of narrow wavelength detection range and material instability of photodetectors, realizes bias-free operation and efficient photodetection, and has good light detection capability and response speed.

CN120751782APending Publication Date: 2025-10-03HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510949062.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-10
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing photodetectors are unable to effectively expand the wavelength detection range. Most of them are based on lead-containing material systems, which are unstable and difficult to modify, and the optical power under zero bias is low.

Method used

A BiVO4-BaTiO3 composite thin film structure was used to prepare a light absorption layer consisting of a BiVO4 layer and a BaTiO3 mesoporous layer by a sol-gel method, and a gold electrode was prepared on it to form an ABABAB type self-powered visible light detector.

Benefits of technology

It has achieved self-powered operation without external bias voltage, broadened the light detection wavelength range to 350nm~450nm, and has high photocurrent and response speed, good stability, and a simple and environmentally friendly preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120751782A_ABST
    Figure CN120751782A_ABST
Patent Text Reader

Abstract

The invention discloses a self-powered visible light detector based on a BiVO4-BaTiO3 composite film and a preparation method of the self-powered visible light detector, and belongs to the technical field of metal oxide semiconductor photoelectric detection. The problems that an existing photoelectric detector cannot effectively widen the wavelength detection range, is mostly based on a lead-containing material system, and is unstable in material, difficult to modify and low in optical power under zero bias voltage are solved. The self-powered visible light detector is composed of a light absorption layer and a gold electrode from bottom to top, wherein the light absorption layer is composed of a conductive substrate and a BiVO4 layer-BaTiO3 mesoporous layer; the preparation method comprises the following steps: 1, preparing the light absorption layer composed of the BiVO4 layer-BaTiO3 mesoporous layer; and 2, preparing a gold electrode. The invention is used for the self-powered visible light detector based on the BiVO4-BaTiO3 composite film and the preparation of the self-powered visible light detector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal oxide semiconductor photoelectric detection. Background Art

[0002] With the development of science and technology, self-powered visible light photodetectors based on the photovoltaic effect of metal oxide semiconductor materials have shown great application prospects. They have become a research focus in the field of self-powered photodetectors because they can exhibit sufficient optical power under specific wavelength light. However, a single material is selective for light within a certain wavelength range, and the excellent performance of the photodetector is related to the optical power density and wavelength composition of the light. Broadening the wavelength detection range of the device is crucial for the practical application of the photodetector.

[0003] The core principle of self-powered photodetectors is similar to that of photovoltaic devices. When a semiconductor absorbs particles with energies above its intrinsic band gap, electrons at the top of the valence band are excited to transition to the conduction band, generating electron and hole carriers. These excited carriers quickly decay to the ground state and maintain energy conservation by emitting photons or phonons. However, when the electrostatic potential in the semiconductor has an asymmetric structure (built-in electric field), it may separate electron and hole carriers, causing them to move in opposite directions, resulting in electron or hole flow, that is, generating current.

[0004] At present, many of the reported photodetectors are based on lead-containing material systems. The instability of the materials, the difficult modification methods, and the low optical power under zero bias are the main reasons restricting the practical application of oxide photovoltaic devices. Summary of the Invention

[0005] The present invention aims to solve the problems that existing photodetectors cannot effectively expand the wavelength detection range, and that most existing photodetectors are based on lead-containing material systems, which are unstable, difficult to modify, and have low optical power under zero bias. The present invention further provides a self-powered visible light detector based on BiVO4-BaTiO3 composite film and a preparation method thereof.

[0006] A self-powered visible light detector based on a BiVO4-BaTiO3 composite film, which consists of a conductive substrate, a light absorption layer consisting of a BiVO4 layer-BaTiO3 mesoporous layer, and a gold electrode from bottom to top;

[0007] The light absorption layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer has an ABABAB structure from bottom to top, wherein A is the BiVO4 layer and B is the BaTiO3 mesoporous layer.

[0008] A method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film is carried out according to the following steps:

[0009] 1. Preparation of a light absorption layer consisting of a BiVO4 layer and a BaTiO3 mesoporous layer:

[0010] ① Add the BiVO4 precursor solution dropwise onto the conductive substrate, rotate it at a speed of 2000 rpm to 3000 rpm for 5 s to 10 s, then rotate it at a speed of 4000 rpm to 6000 rpm for 20 s to 30 s, and then pre-crystallize and solidify it at a temperature of 300 ° C to 350 ° C for 180 s to 200 s, and finally anneal to obtain a BiVO4 layer;

[0011] ② The BaTiO3 precursor solution is added dropwise onto the BiVO4 layer, rotated at a speed of 2000 rpm to 3000 rpm for 5 s to 10 s, then rotated at a speed of 6000 rpm to 8000 rpm for 20 s to 30 s, and then pre-crystallized and solidified at a temperature of 300 ° C to 350 ° C for 180 s to 200 s, and finally annealed to obtain a BaTiO3 mesoporous layer;

[0012] ③ Repeat steps ① to ② twice to obtain an ABABAB structure from bottom to top, i.e., a conductive substrate covered with a light absorbing layer consisting of a BiVO4 layer and a BaTiO3 mesoporous layer, wherein A is the BiVO4 layer and B is the BaTiO3 mesoporous layer;

[0013] 2. Preparation of gold electrode:

[0014] By using magnetron sputtering, a gold electrode is prepared on the light absorption layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer of the conductive substrate, thus completing the preparation method of the self-powered visible light detector based on the BiVO4-BaTiO3 composite film.

[0015] The beneficial effects of the present invention are:

[0016] 1. The self-powered visible light detector based on the BiVO4-BaTiO3 composite film prepared by the present invention has the ability of a self-powered photodetector to work without an external bias voltage, thereby improving the portability of the device.

[0017] 2. The self-powered visible light detector based on the BiVO4-BaTiO3 composite film prepared by the present invention solves the problem of poor light detection capability of a single BiVO4 thin film material for blue light in the wavelength range of 400nm~450nm and a single BaTiO3 thin film material for violet light in the wavelength range of 350nm~380nm. The obtained BiVO4-BaTiO3 composite film has good light detection capability for light in the wavelength range of 350nm~450nm.

[0018] 3. The self-powered visible light detector based on the BiVO4-BaTiO3 composite film prepared by the present invention utilizes the built-in electric field of BiVO4 and BaTiO3 and the heterojunction electric field between the contact surfaces of the two materials. It is tested under dark conditions and has low dark current. Under irradiation with light in the two bands of 365nm violet light and 450nm blue light, it has high photocurrent, fast response speed, and good stability. It can be used for high-performance photoelectric logic gates with high detectivity at 365nm and 450nm.

[0019] 4. The present invention adopts a simple sol-gel method to prepare BiVO4-BaTiO3 composite film material. This method is simple and easy, the equipment is low-cost, there is no pollution to the environment during the experiment, it conforms to the concept of green development, the process cycle is short, and a large number of samples can be prepared in a short time compared with other methods, which greatly saves construction time. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 X-ray diffraction patterns of the BiVO4 layer and the BaTiO3 mesoporous layer and the X-ray photoelectron spectrum of the light absorption layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer prepared in step 1③ of Example 1, (a) is XRD, (b) is the full XPS spectrum, (c) is the XPS spectrum of Ba 3d, (d) is the XPS spectrum of Ti 2p, (e) is the XPS spectrum of Bi 4f, and (f) is the XPS spectrum of V 2p;

[0021] Figure 2 UV-visible absorption spectra of the light-absorbing layer composed of a BiVO4 layer and a BaTiO3 mesoporous layer prepared in step 1 (3) of Example 1, (a) full spectrum from 200 nm to 800 nm, (b) hv and [F(R)hv] 2 The relationship curve of

[0022] Figure 3 The morphology of the light absorption layer composed of a BiVO4 layer and a BaTiO3 mesoporous layer prepared in step 1 (3) of Example 1 is shown: (a) a cross-sectional scanning electron micrograph, and (b) an atomic force micrograph of the surface.

[0023] Figure 4 Schematic diagram of the structure of the self-powered visible light detector based on BiVO4-BaTiO3 composite film of the present invention;

[0024] Figure 5 Performance test of the BiVO4-BaTiO3 composite film self-powered visible light photodetector prepared in Example 1 under zero bias voltage, (a) JV curve under different wavelengths of light, (b) JV curve under 365nm wavelength light, (c) JV curve under 450nm wavelength light, (d) photocurrent density J under 365nm wavelength lightSC and open circuit voltage V OC , (e) Photocurrent density J under 450nm wavelength light SC and open circuit voltage V OC , (f) Jt curves under 365nm and 450nm wavelength light;

[0025] Figure 6 The photocurrent rise and fall response time of the BiVO4-BaTiO3 composite film self-powered visible light photodetector prepared in Example 1 under 365nm and 450nm wavelength illumination under zero bias, (a) photocurrent rise response time under 365nm wavelength illumination, (b) photocurrent fall response time under 365nm wavelength illumination, (c) photocurrent rise response time under 450nm wavelength illumination, (d) photocurrent fall response time under 450nm wavelength illumination;

[0026] Figure 7 Schematic diagram of the UV-visible dual-band coding system of the BiVO4-BaTiO3 composite film self-powered visible light photodetector prepared in Example 1 under zero bias, (a) time-current characteristics under four different irradiation conditions (darkness, purple light, blue light, purple light and blue light), (b) logical relationship between different photocurrent levels and the optical switches of purple light and blue light, where "0" represents the light off and "1" represents the light on, (c) schematic diagram of the coding process. DETAILED DESCRIPTION

[0027] Specific implementation method 1, combined with Figure 4 Specifically, the present embodiment is a self-powered visible light detector based on a BiVO4-BaTiO3 composite film, which consists of a conductive substrate, a light absorption layer composed of a BiVO4 layer-BaTiO3 mesoporous layer, and a gold electrode from bottom to top;

[0028] The light absorption layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer has an ABABAB structure from bottom to top, wherein A is the BiVO4 layer and B is the BaTiO3 mesoporous layer.

[0029] The beneficial effects of this specific embodiment are:

[0030] 1. The self-powered visible light detector based on the BiVO4-BaTiO3 composite film prepared in this specific embodiment has the ability of a self-powered photodetector to work without an external bias voltage, thereby improving the portability of the device.

[0031] 2. The self-powered visible light detector based on the BiVO4-BaTiO3 composite film prepared in this specific embodiment solves the problem of poor light detection capability of a single BiVO4 thin film material for blue light in the wavelength range of 400nm~450nm and a single BaTiO3 thin film material for violet light in the wavelength range of 350nm~380nm. The obtained BiVO4-BaTiO3 composite film has good light detection capability for light in the wavelength range of 350nm~450nm.

[0032] 3. The self-powered visible light detector based on the BiVO4-BaTiO3 composite film prepared in this specific embodiment utilizes the built-in electric field of BiVO4 and BaTiO3 and the heterojunction electric field between the contact surfaces of the two materials. It is tested under dark conditions and has a low dark current. Under irradiation with light in the two bands of 365nm violet light and 450nm blue light, it has a high photocurrent, a fast response speed, and good stability. It can be used for high-performance photoelectric logic gates with high detectivity at 365nm and 450nm.

[0033] 4. This specific embodiment adopts a simple sol-gel method to prepare BiVO4-BaTiO3 composite film material. This method is simple and easy, the equipment is low-cost, there is no pollution to the environment during the experiment, it conforms to the concept of green development, the process cycle is short, and a large number of samples can be prepared in a short time compared with other methods, which greatly saves construction time.

[0034] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the conductive substrate is a Pt conductive substrate. Other aspects are the same as specific embodiment 1.

[0035] Specific embodiment 3: This embodiment is a method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film, which is carried out in the following steps:

[0036] 1. Preparation of a light absorption layer consisting of a BiVO4 layer and a BaTiO3 mesoporous layer:

[0037] ① Add the BiVO4 precursor solution dropwise onto the conductive substrate, rotate it at a speed of 2000 rpm to 3000 rpm for 5 s to 10 s, then rotate it at a speed of 4000 rpm to 6000 rpm for 20 s to 30 s, and then pre-crystallize and solidify it at a temperature of 300 ° C to 350 ° C for 180 s to 200 s, and finally anneal to obtain a BiVO4 layer;

[0038] ② The BaTiO3 precursor solution is added dropwise onto the BiVO4 layer, rotated at a speed of 2000 rpm to 3000 rpm for 5 s to 10 s, then rotated at a speed of 6000 rpm to 8000 rpm for 20 s to 30 s, and then pre-crystallized and solidified at a temperature of 300 ° C to 350 ° C for 180 s to 200 s, and finally annealed to obtain a BaTiO3 mesoporous layer;

[0039] ③ Repeat steps ① to ② twice to obtain an ABABAB structure from bottom to top, i.e., a conductive substrate covered with a light absorbing layer consisting of a BiVO4 layer and a BaTiO3 mesoporous layer, wherein A is the BiVO4 layer and B is the BaTiO3 mesoporous layer;

[0040] 2. Preparation of gold electrode:

[0041] By using magnetron sputtering, a gold electrode is prepared on the light absorption layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer of the conductive substrate, thus completing the preparation method of the self-powered visible light detector based on the BiVO4-BaTiO3 composite film.

[0042] Specific embodiment 4: This embodiment differs from specific embodiment 3 in that: the thickness of the conductive substrate in step 1 (1) is 200 nm to 300 nm; in step 1 (1), the BiVO4 precursor solution is dropwise added to the conductive substrate by spin coating to a thickness of 110 nm to 120 nm; in step 1 (2), the BaTiO3 precursor solution is dropwise added to the BiVO4 layer by spin coating to a thickness of 5 nm to 10 nm; and the thickness of the gold electrode in step 2 is 5 nm to 10 nm. Other aspects are the same as those in specific embodiment 3.

[0043] Specific Embodiment 5: This embodiment differs from either Specific Embodiment 3 or Specific Embodiment 4 in that the conductive substrate described in step 1 (1) is a pretreated conductive substrate, and the pretreatment is specifically performed as follows: ultrasonic cleaning is performed in acetone, 10% to 20% by mass dilute hydrochloric acid, deionized water, and anhydrous ethanol, respectively, for 10 to 20 minutes at an ultrasonic power of 50 W to 80 W, followed by drying at a temperature of 250°C to 300°C. Other steps are the same as Specific Embodiment 3 or 4.

[0044] Specific embodiment six: This embodiment differs from any one of specific embodiments three to five in that: the BiVO4 precursor solution described in step one (1) is specifically prepared according to the following steps: ammonium metavanadate is added to a mixed solution of ethylene glycol and acetic acid, stirred and dissolved at a temperature of 60°C to 70°C for 2h to 3h, cooled to room temperature, and then bismuth nitrate is added and stirred and dissolved at room temperature for 2h to 3h to obtain a BiVO4 precursor solution; the volume ratio of ethylene glycol to acetic acid in the mixed solution of ethylene glycol and acetic acid is (4 to 9):1; the concentration of ammonium metavanadate in the BiVO4 precursor solution is 0.1mol / L to 0.5mol / L; the concentration of bismuth nitrate in the BiVO4 precursor solution is 0.1mol / L to 0.5mol / L. Other steps are the same as specific embodiments three to five.

[0045] Specific embodiment seven: This embodiment is different from any one of specific embodiments three to six in that: the annealing described in step one ① is specifically carried out according to the following steps: under an air atmosphere, first raising the temperature from room temperature to 250℃~260℃, and keeping it at 250℃~260℃ for 10s~20s, then raising the temperature from 250℃~260℃ to 300℃~320℃, and keeping it at 300℃~320℃ for 25s~30s, then raising the temperature from 300℃~320℃ to 400℃~420℃, and keeping it at 400℃~420℃ for 20s~25s, then raising the temperature from 400℃~420℃ to 500℃~510℃, and keeping it at 500℃~510℃ for 300s~400s, and finally cooling with the furnace to below 70℃. The rest is the same as the specific implementation methods three to six.

[0046] Specific embodiment eight: This embodiment differs from any one of specific embodiments three to seven in that: the BaTiO3 precursor solution described in step one (2) is specifically prepared according to the following steps: tetrabutyl titanate is added to a mixed solution of ethylene glycol methyl ether and acetic acid, stirred and dissolved at a temperature of 70°C to 80°C for 2h to 3h, cooled to room temperature, and then barium acetate is added and stirred and dissolved at room temperature for 2h to 3h to obtain a BaTiO3 precursor solution; the volume ratio of ethylene glycol methyl ether to acetic acid in the mixed solution of ethylene glycol methyl ether and acetic acid is (4 to 9):1; the concentration of tetrabutyl titanate in the BaTiO3 precursor solution is 0.1mol / L to 0.5mol / L; the concentration of barium acetate in the BaTiO3 precursor solution is 0.1mol / L to 0.5mol / L. Other aspects are the same as specific embodiments three to seven.

[0047] Specific embodiment nine: This embodiment differs from any one of specific embodiments three to eight in that: the annealing described in step one (2) is specifically carried out according to the following steps: in an air atmosphere, firstly, the temperature is raised from room temperature to 250°C~260°C, and kept at 250°C~260°C for 20s~30s, then the temperature is raised from 250°C~260°C to 300°C~320°C, and kept at 300°C~320°C for 30s~40s, then the temperature is raised from 300°C~ The temperature is raised from 320°C to 400°C~420°C, and kept at 400°C~420°C for 30s~35s, then raised from 400°C~420°C to 500°C~510°C, and kept at 500°C~510°C for 30s~40s, then raised from 500°C~510°C to 600°C~650°C, and kept at 600°C~650°C for 300s~400s, and finally cooled by 70°C to below. Other aspects are the same as those in Specific Embodiments 3 to 8.

[0048] Specific embodiment 10: The difference between this embodiment and any one of the specific embodiments 3 to 9 is that in step 2, a gold electrode is prepared on the light absorbing layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer of the conductive substrate by using magnetron sputtering method. Specifically, the steps are as follows: in a vacuum of 5×10 4 Pa~6×10 4 Pa, adjust the argon flow rate to 100mL / min~200mL / min, then turn on the magnetron sputtering power supply to a current of 150A~180A. After the Au target is ignited, the vacuum degree is 5×10 4 Pa~6×10 4 Under the conditions of 100 mL / min to 200 mL / min of argon gas flow rate and 150 A to 180 A, magnetron sputtering is performed for 5 to 10 minutes. Other steps are the same as those in the third to ninth embodiments.

[0049] The following examples are used to verify the beneficial effects of the present invention:

[0050] Example 1:

[0051] A self-powered visible light detector based on a BiVO4-BaTiO3 composite film, which consists of a conductive substrate, a light absorption layer consisting of a BiVO4 layer-BaTiO3 mesoporous layer, and a gold electrode from bottom to top;

[0052] The light absorption layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer has an ABABAB structure from bottom to top, wherein A is the BiVO4 layer and B is the BaTiO3 mesoporous layer.

[0053] The conductive substrate is a Pt conductive substrate.

[0054] The above-mentioned method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film is carried out according to the following steps:

[0055] 1. Preparation of a light absorption layer consisting of a BiVO4 layer and a BaTiO3 mesoporous layer:

[0056] ① The BiVO4 precursor solution was dropped onto the conductive substrate with a spin coating thickness of 110 nm. The substrate was rotated at 2000 rpm for 10 seconds, then at 4000 rpm for 20 seconds. The substrate was then pre-crystallized and solidified at 300°C for 180 seconds, and finally annealed to obtain a BiVO4 layer.

[0057] ② According to the spin coating thickness of 10nm, the BaTiO3 precursor solution was added dropwise onto the BiVO4 layer, and the spin speed was 2000rpm for 5s, then the spin speed was 8000rpm for 20s, and then the pre-crystallization and curing was carried out at a temperature of 300℃ for 180s, and finally annealed to obtain the BaTiO3 mesoporous layer;

[0058] ③ Repeat steps ① to ② twice to obtain an ABABAB structure from bottom to top, i.e., a conductive substrate covered with a light absorbing layer consisting of a BiVO4 layer and a BaTiO3 mesoporous layer, wherein A is the BiVO4 layer and B is the BaTiO3 mesoporous layer;

[0059] 2. Preparation of gold electrode:

[0060] Using magnetron sputtering, a circular gold electrode with a diameter of r=0.02mm was prepared on the light absorption layer composed of BiVO4 layer-BaTiO3 mesoporous layer on the conductive substrate, and a self-powered visible light detector based on BiVO4-BaTiO3 composite film was obtained.

[0061] The conductive substrate described in step 1① has a size of 10 mm × 10 mm and a thickness of 300 nm; the thickness of the gold electrode is 10 nm.

[0062] The conductive substrate described in step 1① is a pretreated conductive substrate, and the pretreatment is specifically carried out according to the following steps: under an ultrasonic power of 80W, ultrasonic cleaning is carried out in acetone, 10% by mass dilute hydrochloric acid, deionized water and anhydrous ethanol for 10 minutes respectively, and then dried at a temperature of 300°C.

[0063] The BiVO4 precursor solution described in step 1① is specifically prepared according to the following steps: ammonium metavanadate is added to a mixed solution of ethylene glycol and acetic acid, stirred and dissolved at a temperature of 60°C for 2 hours, cooled to room temperature, and then bismuth nitrate is added and stirred and dissolved at room temperature for 2 hours to obtain a BiVO4 precursor solution; the volume ratio of ethylene glycol and acetic acid in the mixed solution of ethylene glycol and acetic acid is 9:1; the concentration of ammonium metavanadate in the BiVO4 precursor solution is 0.3 mol / L; the concentration of bismuth nitrate in the BiVO4 precursor solution is 0.3 mol / L.

[0064] The annealing described in step 1 ① is specifically carried out according to the following steps: in an air atmosphere, first the temperature is raised from room temperature to 250 ℃, and at a temperature of 250 ℃, is kept warm for 10s, then the temperature is raised from 250 ℃ to 300 ℃, and at a temperature of 300 ℃, is kept warm for 25s, then the temperature is raised from 300 ℃ to 400 ℃, and at a temperature of 400 ℃, is kept warm for 20s, then the temperature is raised from 400 ℃ to 500 ℃, and at a temperature of 500 ℃, is kept warm for 300s, and finally the temperature is cooled by furnace cooling to below 70 ℃.

[0065] The BaTiO3 precursor solution described in step 1② is specifically prepared according to the following steps: tetrabutyl titanate is added to a mixed solution of ethylene glycol methyl ether and acetic acid, stirred and dissolved at a temperature of 70°C for 2 hours, cooled to room temperature, and then barium acetate is added, stirred and dissolved at room temperature for 2 hours to obtain a BaTiO3 precursor solution; the volume ratio of ethylene glycol methyl ether and acetic acid in the mixed solution of ethylene glycol methyl ether and acetic acid is 8:2; the concentration of tetrabutyl titanate in the BaTiO3 precursor solution is 0.3 mol / L; the concentration of barium acetate in the BaTiO3 precursor solution is 0.3 mol / L.

[0066] The annealing described in step 1 2. is specifically carried out according to the following steps: under air atmosphere, first the temperature is heated to 250 ℃ from room temperature, and at a temperature of 250 ℃, is incubated for 20s, then the temperature is heated to 300 ℃ from 250 ℃, and at a temperature of 300 ℃, is incubated for 30s, then the temperature is heated to 400 ℃ from 300 ℃, and at a temperature of 400 ℃, is incubated for 30s, then the temperature is heated to 500 ℃ from 400 ℃, and at a temperature of 500 ℃, is incubated for 30s, then the temperature is heated to 600 ℃ from 500 ℃, and at a temperature of 600 ℃, is incubated for 300s, and finally the furnace is cooled by 70 ℃ to below.

[0067] In step 2, a gold electrode is prepared on the light absorbing layer composed of BiVO4 layer and BaTiO3 mesoporous layer of the conductive substrate by magnetron sputtering. The specific steps are as follows:4 Pa, the argon flow rate was adjusted to 100 mL / min, and then the magnetron sputtering power supply was turned on to a current of 180 A. After the Au target was ignited, the vacuum degree was 6×10 4 Under the conditions of Pa, argon flow rate of 100 mL / min and current of 180 A, magnetron sputtering was carried out for 10 min.

[0068] In order to test the BiVO4 layer and the BaTiO3 mesoporous layer respectively, a single-layer BiVO4 thin film and a single-layer BaTiO3 thin film were prepared on two Pt substrates according to the preparation methods in steps 1 ① and ② of Example 1 respectively; Figure 1 The X-ray diffraction patterns of the BiVO4 layer and the BaTiO3 mesoporous layer and the X-ray photoelectron spectrum of the light absorption layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer prepared in step 1③ of Example 1, (a) is XRD, (b) is the full XPS spectrum, (c) is the XPS spectrum of Ba 3d, (d) is the XPS spectrum of Ti 2p, (e) is the XPS spectrum of Bi 4f, and (f) is the XPS spectrum of V 2p XPS spectrum; in Figure (a), by comparing the X-ray diffraction spectrum with the standard PDF cards PDF#97-018-1561 and PDF#97-002-3758, it can be seen that the prepared materials are BiVO4 and BaTiO3. Diffraction peaks such as (-111), (121), (004), (-202), and (060) can be observed in the X-ray diffraction spectrum of BiVO4, and diffraction peaks such as (100), (101), and (111) can be observed in the X-ray diffraction spectrum of BaTiO3. In Figure (b), the XPS full spectrum of the light absorption layer composed of BiVO4 layer and BaTiO3 mesoporous layer can be found from the figure. The characteristic binding energy peaks of Bi 4f, C 1s, Bi 4d, V 2p, O 1s, Ba 3d, and Ti 2p can be found. In Figure (c), the XPS spectra of Ba 3d at 795.6eV and 780.3eV are respectively 3 / 2 and Ba 3d 5 / 2 , indicating that Ba element exists in the film with +2 valence. In Figure (c), the XPS spectrum of Ti 2p at 464.8eV and 458.9eV are Ti 2p 1 / 2 and Ti 2p 3 / 2 , indicating that the Ti element exists in the film with a valence of +4. In Figure (d), the XPS spectrum of Bi 4f at 464.8eV and 458.9eV are Ti 2p 1 / 2 and Ti 2p 3 / 2 , indicating that the Ti element exists in the film with a valence of +4. In Figure (e), the XPS spectrum of Bi 4f at 164.3eV and 158.9eV are Bi 4f 7 / 2 and Bi 4f5 / 2 , indicating that Bi element exists in the film with a valence of +3. In Figure (f), the XPS spectrum of V 2p, the characteristic peaks at 524.3eV and 516.6eV are attributed to V 5+ , the characteristic peaks at 522.9 eV and 515.7 eV can be attributed to V 4+ , indicating that the V element exists in the film in two forms of +4 and +5 valence.

[0069] Figure 2 UV-visible absorption spectra of the light-absorbing layer composed of a BiVO4 layer and a BaTiO3 mesoporous layer prepared in step 1 (3) of Example 1, (a) full spectrum from 200 nm to 800 nm, (b) hv and [F(R)hv] 2 In Figure (a), the light absorption layer composed of BiVO4 layer and BaTiO3 mesoporous layer shows high light absorption characteristics in the range of 300nm~450nm, with the highest light absorption of 51.98% at a wavelength of 380nm. When the wavelength is greater than 450nm, the light absorption performance gradually decreases with the increase of wavelength. 2 The relationship curve shows that the band gap width E of the light absorption layer composed of BiVO4 layer-BaTiO3 mesoporous layer g It is 2.397eV.

[0070] Figure 3 The following are morphological images of the light absorbing layer composed of a BiVO4 layer and a BaTiO3 mesoporous layer prepared in step 1③ of Example 1, (a) a cross-sectional scanning electron microscope image, and (b) a surface atomic force microscope image. In Figure (a), the cross-sectional view of the BiVO4-BaTiO3 composite film shows that the thickness of the light absorbing layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer is 343.5 nm. This is because the holes are filled in each other during the layered spin coating process, resulting in a thickness of the film that is different from the sum of the thicknesses of the single-layer spin coating. In Figure (b), the surface atomic force microscope image of the light absorbing layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer shows that the surface morphology of the film is uniform, and that large ellipsoidal BaTiO3 particles (circled in the figure) are attached to the BiVO4 surface, i.e., the BaTiO3 mesoporous layer is a mesoporous layer composed of BaTiO3 particles.

[0071] At zero bias, in dark conditions, the optical power density is 8mW / cm 2 The 365nm light and the optical power density is 165mW / cm 2 The JV curves of the BiVO4-BaTiO3 composite film self-powered visible light detector prepared in Example 1 were tested under different wavelengths of light. Figure 5(a); Under zero bias, at an optical power density of 2.5 mW / cm 2 、3mW / cm 2 、3.5mW / cm 2 , 5mW / cm 2 , 6mW / cm 2 , 8mW / cm 2 and 10mW / cm 2 The JV curve test and photocurrent density J of the BiVO4-BaTiO3 composite film self-powered visible light detector prepared in Example 1 were carried out under 365nm wavelength light. SC and open circuit voltage V OC Tests such as Figure 5 (b) and 5(d); Under zero bias, the optical power density is 103mW / cm 2 、114mW / cm 2 、125mW / cm 2 、136mW / cm 2 、147mW / cm 2 、155mW / cm 2 and 165mW / cm 2 The JV curve test and photocurrent density J of the BiVO4-BaTiO3 composite film self-powered visible light detector prepared in Example 1 were carried out under 450nm wavelength light. SC and open circuit voltage V OC Tests such as Figure 5 (c) and 5(e); Under zero bias, the optical power density is 8mW / cm 2 The 365nm light and the optical power density is 165mW / cm 2 The Jt curves of the BiVO4-BaTiO3 composite film self-powered visible light detector prepared in Example 1 were tested under different wavelengths of light. Figure 5 (f);

[0072] Figure 5 Performance test of the BiVO4-BaTiO3 composite film self-powered visible light photodetector prepared in Example 1 under zero bias voltage, (a) JV curve under different wavelengths of light, (b) JV curve under 365nm wavelength light, (c) JV curve under 450nm wavelength light, (d) photocurrent density J under 365nm wavelength light SC and open circuit voltage V OC , (e) Photocurrent density J under 450nm wavelength light SC and open circuit voltage V OC(f) Jt curves under 365nm and 450nm wavelength illumination; As shown in Figure (a), the short-circuit current density is close to 0mA / cm under dark conditions. 2 , the open circuit voltage is close to 0 V, and the short circuit current density is 0.13 mA / cm under 365 nm light. 2 , the open circuit voltage is 0.29V, and the short circuit current density is 0.79mA / cm under 450nm light. 2 , the open circuit voltage is 0.39V; as shown in Figure (b), under the irradiation of 365nm light at different light power densities, the BiVO4-BaTiO3 composite film self-powered visible light photodetector shows obvious short-circuit current and open-circuit voltage; as shown in Figure (c), under the irradiation of 450nm light at different light power densities, the BiVO4-BaTiO3 composite film self-powered visible light photodetector shows obvious short-circuit current and open-circuit voltage; as shown in Figure (d), under the light power density of 2.5mW / cm 2 Under 365nm light irradiation, the short-circuit current density is 0.09 mA / cm 2 , the open circuit voltage is 0.27 V; as shown in Figure (e), when the optical power density is 103 mW / cm 2 Under 450nm light irradiation, the short-circuit current density is 0.45mA / cm 2 , the open-circuit voltage is 0.38V; and the photocurrent density under 450nm illumination is higher than that under 365m illumination, because the energy of 450nm is closer to the overall bandgap width of the device; as can be seen from Figure (f), under continuous illumination of 365nm and 450nm wavelengths for more than 400s, the BiVO4-BaTiO3 composite film self-powered visible light photodetector operates stably, indicating that the prepared BiVO4-BaTiO3 composite film self-powered visible light photodetector has long-term stability.

[0073] At zero bias, the optical power density is 8mW / cm 2 The 365nm light and the optical power density is 165mW / cm 2 The photocurrent rise and fall response time of the BiVO4-BaTiO3 composite film self-powered visible light photodetector prepared in Example 1 was tested under 450nm light of different wavelengths; Figure 6Under zero bias, the photocurrent rise and fall response time of the BiVO4-BaTiO3 composite film self-powered visible light photodetector prepared in Example 1 under 365nm and 450nm wavelength illumination, (a) photocurrent rise response time under 365nm wavelength illumination, (b) photocurrent fall response time under 365nm wavelength illumination, (c) photocurrent rise response time under 450nm wavelength illumination, (d) photocurrent fall response time under 450nm wavelength illumination. As can be seen from the figure, the photocurrent rise response time under 365nm wavelength illumination in (a) is 0.58ms, the photocurrent fall response time under 365nm wavelength illumination in (b) is 0.87ms, the photocurrent rise response time under 450nm wavelength illumination in (c) is 0.538ms, and the photocurrent fall response time under 450nm wavelength illumination in (d) is 0.694ms.

[0074] Based on the dual-band detection characteristics of the BiVO4-BaTiO3 composite film self-powered visible light photodetector in the 365nm and 450nm bands, a coding system that can be used as a photoelectric logic "AND" gate is proposed. Four different current levels were measured under four conditions, including dark conditions, light power density of 8mW / cm 2 365nm light, light power density is 165mW / cm 2 450nm light, light power density is 8mW / cm 2 365nm light + optical power density of 165mW / cm 2 450nm light; Figure 7 Schematic diagram of the UV-visible dual-band coding system of the BiVO4-BaTiO3 composite film self-powered visible light photodetector prepared in Example 1 under zero bias, (a) time-current characteristics under four different conditions (darkness, purple light, blue light, purple light and blue light), (b) logical relationship between different photocurrent levels and the optical switches of purple light and blue light, where "0" represents the light off and "1" represents the light on, (c) schematic diagram of the coding process. It can be seen from the current-time curve (Jt) in the figure that under 365nm light, the maximum photocurrent density at zero bias reaches 0.12mA / cm 2 Under 450nm light, the maximum photocurrent density at zero bias reaches 0.83mA / cm 2 Under the combined irradiation of 365nm and 450nm light, the maximum photocurrent density at zero bias reaches 0.95mA / cm 2The four lighting conditions, represented by "00," "01," "10," and "11," represent "darkness," "365nm illumination," "450nm illumination," and "365nm + 450nm illumination," respectively, corresponding to increasing current levels. According to the logic of the AND gate, the output signal is "1" only when the input light signal is "11." In this case, the device's current level is the highest, encoding information.

Claims

1. A self-powered visible light detector based on BiVO4-BaTiO3 composite film, characterized in that It consists of a conductive substrate, a light absorption layer consisting of a BiVO4 layer-BaTiO3 mesoporous layer, and a gold electrode from bottom to top; The light absorption layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer has an ABABAB structure from bottom to top, wherein A is the BiVO4 layer and B is the BaTiO3 mesoporous layer.

2. A self-powered visible light detector based on BiVO4-BaTiO3 composite film according to claim 1, characterized in that The conductive substrate is a Pt conductive substrate.

3. The method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film according to claim 1, characterized in that It is carried out in the following steps:

1. Preparation of a light absorption layer consisting of a BiVO4 layer and a BaTiO3 mesoporous layer: ① Add the BiVO4 precursor solution dropwise onto the conductive substrate, rotate it at a speed of 2000 rpm to 3000 rpm for 5 s to 10 s, then rotate it at a speed of 4000 rpm to 6000 rpm for 20 s to 30 s, and then pre-crystallize and solidify it at a temperature of 300 ° C to 350 ° C for 180 s to 200 s, and finally anneal to obtain a BiVO4 layer; ② The BaTiO3 precursor solution is added dropwise onto the BiVO4 layer, rotated at a speed of 2000 rpm to 3000 rpm for 5 s to 10 s, then rotated at a speed of 6000 rpm to 8000 rpm for 20 s to 30 s, and then pre-crystallized and solidified at a temperature of 300 ° C to 350 ° C for 180 s to 200 s, and finally annealed to obtain a BaTiO3 mesoporous layer; ③ Repeat steps ① to ② twice to obtain an ABABAB structure from bottom to top, i.e., a conductive substrate covered with a light absorbing layer consisting of a BiVO4 layer and a BaTiO3 mesoporous layer, wherein A is the BiVO4 layer and B is the BaTiO3 mesoporous layer; 2. Preparation of gold electrode: By using magnetron sputtering, a gold electrode is prepared on the light absorption layer composed of the BiVO4 layer and the BaTiO3 mesoporous layer of the conductive substrate, thus completing the preparation method of the self-powered visible light detector based on the BiVO4-BaTiO3 composite film.

4. The method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film according to claim 3, characterized in that The thickness of the conductive substrate described in step 1① is 200nm~300nm; in step 1①, the BiVO4 precursor solution is added dropwise onto the conductive substrate according to the spin coating thickness of 110nm~120nm; in step 1②, the BaTiO3 precursor solution is added dropwise onto the BiVO4 layer according to the spin coating thickness of 5nm~10nm; the thickness of the gold electrode described in step 2 is 5nm~10nm.

5. The method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film according to claim 3, characterized in that The conductive substrate described in step 1① is a pretreated conductive substrate, and the pretreatment is specifically carried out according to the following steps: under an ultrasonic power of 50W~80W, ultrasonic cleaning is carried out in acetone, 10%~20% dilute hydrochloric acid, deionized water and anhydrous ethanol for 10min~20min respectively, and then drying at a temperature of 250℃~300℃.

6. The method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film according to claim 3, characterized in that The BiVO4 precursor solution described in step 1① is specifically prepared according to the following steps: ammonium metavanadate is added to a mixed solution of ethylene glycol and acetic acid, stirred and dissolved at a temperature of 60°C to 70°C for 2h to 3h, cooled to room temperature, and then bismuth nitrate is added, stirred and dissolved at room temperature for 2h to 3h to obtain a BiVO4 precursor solution; the volume ratio of ethylene glycol and acetic acid in the mixed solution of ethylene glycol and acetic acid is (4~9):1; the concentration of ammonium metavanadate in the BiVO4 precursor solution is 0.1mol / L~0.5mol / L; the concentration of bismuth nitrate in the BiVO4 precursor solution is 0.1mol / L~0.5mol / L.

7. The method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film according to claim 3, characterized in that The annealing described in step 1 ① is specifically carried out according to the following steps: under an air atmosphere, first the temperature is raised from room temperature to 250 ℃ ~ 260 ℃, and at a temperature of 250 ℃ ~ 260 ℃, be incubated for 10s ~ 20s, then the temperature is raised from 250 ℃ ~ 260 ℃ to 300 ℃ ~ 320 ℃, and at a temperature of 300 ℃ ~ 320 ℃, be incubated for 25s ~ 30s, then the temperature is raised from 300 ℃ ~ 320 ℃ to 400 ℃ ~ 420 ℃, and at a temperature of 400 ℃ ~ 420 ℃, be incubated for 20s ~ 25s, then the temperature is raised from 400 ℃ ~ 420 ℃ to 500 ℃ ~ 510 ℃, and at a temperature of 500 ℃ ~ 510 ℃, be incubated for 300s ~ 400s, and finally cool down by furnace cooling to below 70 ℃.

8. The method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film according to claim 3, characterized in that The BaTiO3 precursor solution described in step 1② is specifically prepared according to the following steps: tetrabutyl titanate is added to a mixed solution of ethylene glycol methyl ether and acetic acid, stirred and dissolved for 2h~3h at a temperature of 70℃~80℃, cooled to room temperature, and then barium acetate is added, stirred and dissolved at room temperature for 2h~3h to obtain a BaTiO3 precursor solution; the volume ratio of ethylene glycol methyl ether and acetic acid in the mixed solution of ethylene glycol methyl ether and acetic acid is (4~9):1; the concentration of tetrabutyl titanate in the BaTiO3 precursor solution is 0.1mol / L~0.5mol / L; the concentration of barium acetate in the BaTiO3 precursor solution is 0.1mol / L~0.5mol / L.

9. The method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film according to claim 3, characterized in that The annealing described in step 1② is specifically carried out according to the following steps: in an air atmosphere, first, the temperature is raised from room temperature to 250℃~260℃, and at a temperature of 250℃~260℃, it is kept warm for 20s~30s, then the temperature is raised from 250℃~260℃ to 300℃~320℃, and at a temperature of 300℃~320℃, it is kept warm for 30s~40s, and then the temperature is raised from 300℃~320℃ to 400℃~420℃. ℃, and keep it at 400℃~420℃ for 30s~35s, then increase the temperature from 400℃~420℃ to 500℃~510℃, and keep it at 500℃~510℃ for 30s~40s, then increase the temperature from 500℃~510℃ to 600℃~650℃, and keep it at 600℃~650℃ for 300s~400s, and finally cool down by 70℃ to below with the furnace.

10. The method for preparing a self-powered visible light detector based on a BiVO4-BaTiO3 composite film according to claim 3, characterized in that In step 2, a gold electrode is prepared on the light absorbing layer composed of BiVO4 layer and BaTiO3 mesoporous layer of the conductive substrate by magnetron sputtering. The specific steps are as follows: 4 Pa~6×10 4 Pa, adjust the argon flow rate to 100mL / min~200mL / min, then turn on the magnetron sputtering power supply to a current of 150A~180A. After the Au target is ignited, the vacuum degree is 5×10 4 Pa~6×10 4 Under the conditions of Pa, argon flow rate of 100mL / min~200mL / min and current of 150A~180A, magnetron sputtering is carried out for 5min~10min.